Establishment and Application of Multiple Cross Displacement Amplification Coupled With Lateral Flow Biosensor (MCDA-LFB) for Visual and Rapid Detection of Candida albicans in Clinical Samples - Zhao, Fan; Niu, Lina; Yan, Linlin; Nong, Jinqing; Wang, Chunmei; Wang, Jing; Gao, Naishu; Zhu, Xiaoxue; Wu, Lei; Zheng, Fengzhi; Hu, Shoukui (Frontiers in Cellular and Infection Microbiology, 2019)
Candida albicans is an opportunistic pathogenic yeast that predominantly causes invasive candidiasis. The conventional diagnosis of C. albicans infection depends on time-consuming, culture-based gold-standard methods. Here, a multiple cross displacement amplification (MCDA) assay, combining with a gold nanoparticle-based lateral flow biosensor (LFB) visualization method, was developed for the rapid detection of C. albicans. The internal transcribed spacer II, a region between 5.8S and 28S fungal ribosomal DNA, is a C. albicans species-specific sequence that was used as the MCDA assay target. As an isothermal amplification method, the MCDA reaction with optimized conditions could be completed within only 40 min at a constant temperature (64°C). Then, the amplification reaction products could be visibly detected by a LFB without special equipment. The developed MCDA-LFB assay for C. albicans detection was a specific and accurate method, and could distinguish C. albicans from other pathogens. Just 200 fg of genomic DNA template from pure cultures of C. albicans could be detected using the MCDA-LFB method. The limit of detection (LOD) of the new method was more sensitive than that of both qPCR and loop-mediated isothermal amplification (LAMP). Of 240 clinical sputum samples, all of the C. albicans-positive (87/240) samples identified by the gold-standard method were successfully detected by the MCDA-LFB assay. Moreover, the true positive rate of the newly developed assay was not only higher than that of qPCR (100% vs. 86.2%), but also higher than that of LAMP (100% vs. 94.3%). Thus, the MCDA-LFB assay might be a simple, specific, and sensitive method for the rapid diagnosis of C. albicans in clinical samples.